Production of heterologous cutinases by E. coli and improved enzyme formulation for application on plastic degradation - Gomes, Daniela S. (2013)
Background: The hydrolytic action of cutinases has been applied to the degradation of plastics. Polyethylene terephthalate (PET) have long half-life which constitutes a major problem for their treatment as urban solid residues. The aim of this work was to characterize and to improve stable the enzyme to optimize the process of degradation using enzymatic hydrolysis of PET by recombinant cutinases. Results: The wild type form of cutinase from Fusarium solani pisi and its C-terminal fusion to cellulose binding domain N1 from Cellulomonas fimi were produced by genetically modified Escherichia coli. The maximum activity of cutinases produced in Lactose Broth in the presence of ampicillin and isopropyl β- D-1-thiogalactopyranoside (IPTG) was 1.4 IU/mL. Both cutinases had an optimum pH around 7.0 and they were stable between 30 and 50ºC during 90 min. The addition of glycerol, PEG-200 and (NH4)2SO4 to the metabolic liquid, concentrated by ultra filtration, stabilized the activity during 60 days at 28ºC. The treatment of PET with cutinases during 48 hrs led to maxima weight loss of 0.90%. Conclusions: Recombinant microbial cutinases may present advantages in the treatment of poly(ethylene terephthalate) PET through enzymatic treatments.